1
$\begingroup$

To prove:

$(X+Y)(X'+Z) = XZ + X'Y$

I try to simply $(X+Y)(X'+Z)$ to $XZ + X'Y + YZ$

then I have no idea how to simply further.

Thanks in advance!!

$\endgroup$
0
$\begingroup$

Write $YZ = (X+X^\prime)YZ = XYZ+X^\prime YZ$, then $$\begin{array}{rcl} XZ+X^\prime Y+YZ &=& XZ+X^\prime Y +XYZ+X^\prime YZ \\ &=& XZ(1+Y)+X^\prime Y(1+Z) \\ &=& XZ+X^\prime Y. \end{array}$$

$\endgroup$
2
$\begingroup$

$$\begin{align} (X + Y)(X' + Z) & = (X+Y)X' + (X+Y)Z \\ \\ & = \underbrace{X'X}_{= 0} + X'Y + XZ + YZ \\ \\ & = X'Y + XZ + YZ \\ \\ & = X'Y + XZ + \underbrace{(X+ X')}_{= 1}YZ \\ \\ & = X'Y + XZ + XYZ + X'YZ \\ \\ & = X'Y\underbrace{(1 + Z)}_{= 1} + XZ\underbrace{(1 + Y)}_{= 1} \\ \\ &= X'Y + XZ \end{align}$$

$\endgroup$
  • $\begingroup$ $\ddot\smile$ +) $\endgroup$ – mrs Oct 16 '13 at 9:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.